A criança, o jovem e sua permanente busca de identidades em tempos de novos meios e pós-modernidade - PRADO, Luiz Alberto Serenini (2009)
This work analyses the path that has been delimited and illustrated by the terms "culture", "communication", and "consumption", considering their superposition through the ages and the influences caused over the society behavior. Since the origins of "culture" and its multiple meanings, the transit from the manuscript to the typographic man, until we get the worship of transience, presenteeism and globalization which are peculiarities of postmodernism, it is willed to verify, from the theoretical base point of view, how these phenomena have contributed for the formation of the identity in the general society and in the specific public, circumscript between childhood and adolescenc